DNAJB1-PRKACA is specific for fibrolamellar carcinoma - Graham, Rondell P.; Waldburger, Nina; Rössler, Stephanie; Longerich, Thomas; Schirmacher, Peter (Modern pathology, 2015)
Fibrolamellar carcinoma is a distinct subtype of hepatocellular carcinoma that predominantly affects young patients without underlying cirrhosis. A recurrent DNAJB1-PRKACA fusion has recently been reported in fibrolamellar carcinomas. To determine the specificity of this fusion and to develop routinely available clinical methods of detection, we developed an RT-PCR assay for paraffin-embedded tissues and a FISH probe for detection of the rearrangements of the PRKACA locus. We also developed an RNA in situ hybridization assay to assess expression levels of the total chimeric transcript and wild-type transcripts. A total of 106 primary liver tumors were studied by RT-PCR, including 26 fibrolamellar carcinomas (4 of which were metastases to the abdominal wall or lymph nodes), 25 conventional hepatocellular carcinomas, 25 cholangiocarcinomas, 25 hepatic adenomas, and 5 hepatoblastomas. RT-PCR was successful in 92% of tested fibrolamellar carcinoma cases (24/26) and the DNAJB1-PRKACA fusion transcript was found in all fibrolamellar carcinomas but not in other tumor types. FISH was tested in 19 fibrolamellar carcinomas and in 6 scirrhous hepatocellular carcinomas, which can closely mimic fibrolamellar carcinoma. Rearrangements of the PRKACA locus was seen in all 19 fibrolamellar carcinoma specimens, but in none of the scirrhous hepatocellular carcinomas. Finally, a RNA in situ hybridization strategy was positive in 7/7 successfully hybridized cases, and showed mRNA over-expression in all of the fibrolamellar carcinomas. In addition, the stromal cells embedded in the characteristic intratumoral fibrosis of fibrolamellar carcinomas and the background liver tissues were negative for the DNAJB1-PRKACA fusion by all tested methods. In conclusion, detection of DNAJB1-PRKACA is a very sensitive and specific finding in support of the diagnosis of fibrolamellar carcinoma.
Gesehen am 26.04.2017